(untitled) (Colombia Medica, 2017)
The immune system interacts closely with tumors during the disease development and progression to metastasis. This complex communication between the immune system and the tumor cells can prevent or promote tumor growth. New therapeutic approaches harnessing protective immunological mechanisms have recently shown very promising results. This is performed by blocking inhibitory signals or by activating immunological effector cells directly. Immune checkpoint blockade with monoclonal antibodies directed against the inhibitory immune receptors CTLA-4 and PD-1 has emerged as a successful treatment approach for patients with advanced melanoma. Ipilimumab is an anti-CTLA-4 antibody which demonstrated good results when administered to patients with melanoma. Gene therapy has also shown promising results in clinical trials, particularly, Herpes simplex virus (HSV)-mediated delivery of the HSV thymidine kinase (TK) gene to tumor cells in combination with ganciclovir (GCV) may provide an effective suicide gene therapy for destruction of glioblastomas, prostate tumors and other neoplasias by recruiting tumor-infiltrating lymphocytes into the tumor. Development of new treatment strategies or combination of available innovative therapies to improve cell cytotoxic T lymphocytes trafficking into the tumor mass and the production of inhibitory molecules blocking tumor tissue immunotolerance are crucial to improve the efficacy of cancer therapy.